Can the U.S. interbank market be revived? - Kyungmin Kim; Antoine Martin; Ed Nosal (Federal Reserve Bank of Atlanta, 2018)
Large-scale asset purchases by the Federal Reserve as well as new Basel III banking regulations have led to important changes in U.S. money markets. Most notably, the interbank market has essentially disappeared with the dramatic increase in excess reserves held by banks. We build a model in the tradition of Poole (1968) to study whether interbank market activity can be revived if the supply of excess reserves is decreased sufficiently. We show that it may not be possible to revive the market to precrisis volumes due to costs associated with recent banking regulations. Although the volume of interbank trade may initially increase as excess reserves are decreased from their current abundant levels, the new regulations may engender changes in market structure that result in interbank trading being completely replaced by nonbank lending to banks when excess reserves become scarce. This nonmonotonic response of interbank trading volume to reductions in excess reserves may lead to misleading forecasts about future fed funds prices and quantities when/if the Fed begins to normalize its balance sheet by reducing excess reserves.
Keywords: E42; E58; 330; interbank market; monetary policy implementation; balance sheet costs